2013
DOI: 10.1094/pdis-11-12-1108-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Banana mild mosaic virus Infecting Plantain in Ivory Coast

Abstract: oculated Chenopodium quinoa, C. amaranticolor, Nicotiana benthamiana, N. tabacum (cvs. Havana, Glurk and Turkish), N. glutinosa. Datura stramonium, common bean (cvs. Topcrop and Pinto bean), pumpkin (cv. Small Sugar), pepper (Capsicum annuum, cv. Yolo Wonder) and cucumber (cvs. Emparator and Poinsett 76) plants (results of three independent experiments with six plants per experiment). Symptomless infections were detected in pepper (24 of 30), N. benthamiana (25 of 25), and N. tabacum cv. Turkish (11 of 24) pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, in the 13 regions visited, the viruses identified could infect local cultivars of plantains namely French and False-Horn plantains. Viruses were mentioned on plantains by Kouadio et al (2013) in Cote d"Ivoire, but this study provides some missing information to date on the prevalence of the viruses in the main production areas in relation to cropping systems including plantain. The results showed a predominance of BSOLV and BanMMV in the 13 regions visited and in different cropping systems including plantain.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, in the 13 regions visited, the viruses identified could infect local cultivars of plantains namely French and False-Horn plantains. Viruses were mentioned on plantains by Kouadio et al (2013) in Cote d"Ivoire, but this study provides some missing information to date on the prevalence of the viruses in the main production areas in relation to cropping systems including plantain. The results showed a predominance of BSOLV and BanMMV in the 13 regions visited and in different cropping systems including plantain.…”
Section: Discussionmentioning
confidence: 92%
“…The works carried out on the economic impacts of BSV showed that yield losses could reach 70% after a growth cycle on the cultivar Poyo (Cavendish, AAA genome) in the location of Azaguié (Lassoudière, 1979). On plantain (AAB genome), the only study by Kouadio et al (2013) reported for the first time the presence of BanMMV. However, to date no study has been conducted to determine the prevalence and geographical distribution of the three viruses already identified as well as those known worldwide in the production areas on plantains (AAB genome) in the country.…”
Section: Introductionmentioning
confidence: 99%